Influence of Lubrication Water Contamination by Solid Particles of Mineral Origin on Marine Strut Propeller Shafts Bearings of Ships - Litwin Wojciech; Barszczewska Agnieszka; Piątkowska Ewa; Szwoch Izabela; Matuszewski Leszek; Kahsin Maciej (Polish Maritime Research)
The stern tube or strat bearings are key important component for safety of shipping. Modern global regulations required a low as possible negative impact on environment including lubricants leaking to the sea. The ship owners are looking for reliable and durable solutions. The costs of each ship components are carefully studied. The water lubricated bearings for ship propeller shafts are an environmentally friendly solution. That is the reason why water lubrication is an interesting option to consider. Because simplicity of the ship design is expected the open lubricating system with only one seal module, when sea water is a lubricant is often recommended by manufacturer.